GAMBARAN POLA MAKAN ANAK USIA 3-5 TAHUN DENGAN GIZI KURANG DI PONDOK BERSALIN TRI SAKTI BALONG TANI KECAMATAN JABON –SIDOARJO: DESCRIPTION OF THE DIET PATTERNS OF CHILDREN AGED 3-5 YEARS WITH POOR NUTRITION AT TRI SAKTI BALONG TANI maternity cots, JABON DISTRICT – SIDOARJO - Arifin, Zainul (Universitas Muhammadiyah Sidoarjo, 2015)
Malnutrition is an healthy state (pathological) arising from not eating enough protein and thus less energy consumption during a certain period. In maternal and neonatal clinic Tri Sakti Balong Tani distric Jabon are found malnutrition in children aged 3-5 years (17,5%). Research purposes to identify the picture of the diet of children aged 3-5 years with malnutrition in maternal and neonatal clinic Tri Sakti Balong Tani distric Jabon. The study design was a descriptive survey. The study population was children was 3-5 years who are underweight who recorded in maternal and neonatal clinic Tri Sakti Balong Tani distric Jabon. The study sample was taken the period Oktober 2013 a number of 10 children, all of the subject research. Instrument used are questionnaire. The data obtained are presented using frequency tables and cross tabulation were analyzed statistically untested. The result showed that the age of children aged 3-5 years who are underweight mostly poor diet 80%, toodlers who have a good diet but affect less 20%. Conclusion of the majority of children aged 3-5 years had a poor diet. Suggested to improve the quality of care services institutions in the from of counseling and educational information on nutrition of children aged 3-5 years with a demonstration of the method of food preparation and cooking of menu right.